(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In “In Cuba I Was a German Shepherd,” the story revolves around memory and how memory shapes desire to re-create a Cuban culture abroad. In a post-colonial Cuban setting, Ana Menendez reflects on a question of translating a culture from one geographical location to another and the process of constructing a cultural identity in exile. The very fact underlines here is how ‘Cuban culture is being translated in Domino Park through the protagonist’s expression (voice and memory). The aim of this paper is to show the cross-cultural dynamics of narrative excellence through the memory and experience of the protagonist (Maximo), in capturing the realities as a reflection of shared history and shared losses.